2007
DOI: 10.1002/tox.20251
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between clinical features and blood levels of pentachlorodibenzofuran in patients with Yusho

Abstract: The mean blood level of 2,3,4,7,8-pentachlorodibenzofuran (PeCDF) in 359 patients with Yusho was 177.50 pg/g lipids, which was much higher than that of normal controls (15.2 +/- 8.9 pg/g lipids). The blood levels of PeCDF were significantly correlated with total PCB levels, hexachlorobiphenyl levels, urinary sugar, 2-h erythrocyte sedimentation rate, thymol turbidity test, and sodium levels. A significant correlation was also noted with dermatological findings (acneform eruption and comedones), mucosal finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…The concentration of 2,3,4,7,8-PeCDF in the blood of Yusho patients collected from 2001 to 2003 was significantly correlated with the incidences of acneiform eruptions, comedones and oral mucosal pigmentation (Imamura et al, 2007). The concentrations of 2,3,4,7,8-PeCDF, PCBs and polychlorinated quarterphenyls in blood collected from 2001 to 2004 tended to correlate with the prevalence of acneiform eruptions, black comedones, mucocutaneous pigmentation and hypersecretion of meibomian glands (Kanagawa et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…The concentration of 2,3,4,7,8-PeCDF in the blood of Yusho patients collected from 2001 to 2003 was significantly correlated with the incidences of acneiform eruptions, comedones and oral mucosal pigmentation (Imamura et al, 2007). The concentrations of 2,3,4,7,8-PeCDF, PCBs and polychlorinated quarterphenyls in blood collected from 2001 to 2004 tended to correlate with the prevalence of acneiform eruptions, black comedones, mucocutaneous pigmentation and hypersecretion of meibomian glands (Kanagawa et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…A recent report showed that constitutive activation of AhR and increased expression of Cyp1a1, Gsta1, Fos and TGFA are underlying factors in the development of chloracne in human subjects occupationally or accidentally exposed to significant doses of polycyclic aromatic hydrocarbons (Imamura et al, 2007;Tang et al, 2008). Regeneration studies in adult zebra fish have revealed that AhR2 activation by acute exposure to dioxin (TCDD,2,3,7,dioxin) impairs caudal (tail) fin regeneration (Andreasen et al, 2007), which suggests that AhR has an inhibitory role in tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of 2,3,4,7,8-PeCDF in the blood collected from Yusho patients from 2001 to 2003 was significantly correlated with the presence of comedones, acneiform eruption, oral pigmentation, and numbness of the hands and legs, total PCB levels, urinary sugar, and erythrocyte sedimentation rate, and so on (Imamura et al, 2007), the majority of which are included in the diagnostic criteria of Yusho (Table 1). Furthermore, the 2,3,4,7,8-PeCDF level was found to be significantly related to arthralgia, the concentrations of PCBs to ophthalmologic symptoms, and the concentration of PCQ to increased total cholesterol (Kanagawa et al, 2008).…”
Section: The Association Of Blood Levels Of Pcbs/dioxins With Symptommentioning
confidence: 96%
“…As the blood levels of dioxins, especially 2,3,4,7,8-PeCDF, are positively correlated with various symptoms of Yusho (Imamura et al, 2007;Kanagawa et al, 2008;Matsumoto et al, 2010a), several studies of the medicines that can accelerate the excretion of dioxins or convert dioxins to harmless metabolites have been performed. In experimental models, the oral administration of antidotes such as squalene or charcoal beads in rats increased the excretion of 2,3,4,7,8-PeCDF by two to five times, compared with the level excreted in a control group (Yoshimura et al, 1985;Kamimura et al, 1988).…”
Section: Clinical Studiesmentioning
confidence: 99%